When two worlds collide: Using social media to benchmark public sector performance. Issue 9 (10th August 2015) - Unknown
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – In the early days of corporate social responsibility (CSR) as a newly defined issue in the 1980s, one of the main barriers to achieving a satisfactory level of accountability and reporting was the inability to fully understand the inner workings of major corporations. This was gradually overcome by developments in corporate reporting and regulation that many governments put in place, but for some firms, CSR reporting was something of a hindrance and something that might be manipulated if need be. Or in some countries, simply ignored. Practical implications: – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.